2014
DOI: 10.1111/1365-2664.12195
|View full text |Cite
|
Sign up to set email alerts
|

Hot spots and hot moments of diamondback terrapin road‐crossing activity

Abstract: Summary1. Road mortality is a major component of human impacts on wildlife populations, and the pervasiveness of roads on the landscape presents a substantial challenge for managing those impacts. The feasibility of methods to reduce road mortality depends on the degree to which this threat is spatially or temporally concentrated, which can be based on habitat, human activities or species' ecology. Diamondback terrapins Malaclemys terrapin are a species of conservation concern across their range, and road mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Surveys were carried out between 3 h before and 3 h after the scheduled high tide, coinciding with peaks of nesting activity (Crawford et al . ). We only intercepted females after observing nesting activity and palpated individuals to confirm that all eggs were deposited at that location.…”
Section: Methodsmentioning
confidence: 97%
“…Surveys were carried out between 3 h before and 3 h after the scheduled high tide, coinciding with peaks of nesting activity (Crawford et al . ). We only intercepted females after observing nesting activity and palpated individuals to confirm that all eggs were deposited at that location.…”
Section: Methodsmentioning
confidence: 97%
“…In fact, many of the research studies undertaken on road mortality tended to explore the differences between and within species with the intention of informing more targeted mitigation. For instance, studies considered in this review found that a variety of species-associated factors influenced the rate of wildlife-vehicle collisions, such as age (particularly dispersing juveniles; [19][20][21][22][23]), activity patterns (such as nocturnal and migratory activities; [6,7,24,25]), season (primarily breeding season; [12,[26][27][28][29]), gender (such as males ranging further in the breeding season in search a mate; [23,26,[30][31][32]), diet preferences (e.g., one study found that omnivorous mammals and herbivorous birds were most vulnerable; [33]), mobility (including low-flying species; [15,21,34,35]), behavioral responses (e.g., certain species do not respond to oncoming traffic; [15,36]), and home range size (i.e., the larger the home range the higher the probability of crossing a road; [37]). Another study found that species that were more inconspicuous on the roads were more vulnerable to wildlife-vehicle collisions [38].…”
Section: Direct Impacts Of Roads On Wildlifementioning
confidence: 99%
“…, Crawford et al. ). Within the flourishing subdiscipline of road ecology, however, rarely are both intrinsic and extrinsic factors explicitly and quantitatively assessed within the same system.…”
Section: Introductionmentioning
confidence: 99%